Academic Pressure and Emotional Well-Being in Higher Education: The Role of Negative Emotions in College Students’ Academic Performance - Lu'luuzzahro, Alfina; Dewi Puspitasari; Khristianto (Nexus Publishing, 2025)
This study explores the influence of academic pressure on college students’ emotional well-being and academic performance, with particular attention to the role of negative emotions. Academic pressure often arises from multiple sources, including heavy academic workloads, high parental expectations, strong self-imposed expectations, and limited peer support. These pressures may create challenging learning conditions that affect students’ emotional states and their ability to perform academically. Drawing on students’ narratives as the primary data source, this study examines how academic pressure contributes to stress, anxiety, fear of failure, and tendencies toward social withdrawal. The study aims to examine seven key aspects related to academic pressure, including negative emotional experiences, sources of academic stress, and the relationships between parental expectations, self-expectations, workload demands, and peer support in shaping students’ stress levels. Participants were selected using proportional stratified random sampling to represent diverse student groups. The findings indicate that high parental expectations often encourage perfectionism and fear of failure, while high self-expectations are associated with feelings of inadequacy and frustration. Heavy workloads contribute to academic burnout, reflected in emotional exhaustion, and reduced motivation. Limited peer support further intensifies negative emotions and weakens students’ sense of belonging.